Financial and technical proposal of procurement of lift & escalators, HVAC system, fire detection & protection, generator, sub-station, BBT, MDB and SDB, solar panel, lightning protection - Brac University (Brac University, 2023)
This record consists of general correspondence regarding financial and technical proposal of procurement of lift & escalators, HVAC system, fire detection & protection, generator, sub-station, BBT, MDB and SDB, solar panel, lightning protection of BRAC University new campus project.